The Role of Fiscal Institutions in Managing the Oil Revenue Boom. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines the fiscal responses of oil-producing countries (OPCs) to the oil boom through 2005 and the role of special fiscal institutions (SFIs)-oil funds, fiscal rules and fiscal responsibility legislation (FRL), and budgetary oil prices-in fiscal management in OPCs, and draws some general lessons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet